EFFECT OF CUTTING PARAMETERS ON LOW CARBON STEEL SURFACE ROUGHNESS IN THE CONVENTIONAL TURNING PROCESS - Fahrizal Fahrizal; Priyono Priyono; Sealtial Mau; Anastasia De Delia Dos Santos (JURNAL PENDIDIKAN TEKNIK MESIN, 2022)
In the turning process, the surface roughness is affected by cutting parameters  such as cutting speed, depth of cut, feed rate, and so on. However, there is not much information about the relationship or interaction between cutting parameters and the resulting surface roughness. This study aimed to examine the effect of cutting parameters on the surface roughness value of low carbon steel. This research was conducted experimentally using a conventional lathe with a HSS insert without the use of cutting fluids. It was concluded that the cutting parameters had a significant effect on the surface roughness. The lowest surface roughness value was obtained at 280 rpm spindle speed, 0.5 mm depth of cut and 0.2 mm/rev. feed rate with a roughness value of 2.968 µm. The contribution of each parameter to the surface roughness were 42.2% of spindle speed, 10% of depth of cut and 20.3% of feed rate respectively.